INTERNALISASI NILAI-NILAI PANCASILA DALAM KEGIATAN EKSTRA KURIKULER - Tafonao, Hedrianus (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
Pancasila is the evolution of the noble principles adhered to by the Indonesian people which are universally recognized and become the basis for all other sources. Chosen by non-Western countries or nations, Pancasila is the paradigmatic direction of science, especially the social sciences. Because non-Western countries have different histories, cultures, and ways of life, they must engage with contemporary science. Ranto stated that (2012:1). "The life of the nation and the foundation of the state is Pancasila." what Bung Karno then proposed as the basis for an independent Indonesian state, before the BPUPKI session on June 1 1945. Pancasila is an ideology and philosophy that embodies the identity and vision of the Indonesian nation. Descriptive research with a qualitative approach is the methodology used in this research. The data sources for this research are the school principal, a teacher, and four (four) students who act as informants. Steps one to three of the data collection process are observation, interviews, and documentation research. Through three activity streams, data analysis is completed. Data reduction, data presentation, and conclusions are the first three steps. Apart from being a vital resource for students, teachers also help students become superior humans by using Pancasila Values to humanize themselves. Without teachers, students will only determine the direction of their lives.